Certificate of Recognition presented to eBario Innovation Village, 28 May 2013 - Universiti Malaysia Sarawak, ISITI-CoERI (Universiti Malaysia Sarawak, (UNIMAS), 2013)
As Winner of Global Community's Choice Award for Best Telecentre Innovations